Konverze elektrárny Holešovice - Housková, Dana; Housková Dana (České vysoké učení technické v Praze, 2016)
Diplomová práce zpracovává objekt bývalé strojovny a kotelny v areálu holešovické elektrárny, dnes teplárny. Jedná se o konverzi historických výrobních hal, které jsou nově využity pro kulturu a zábavu. Práce navazuje na předdiplomní projekt, který řešil urbanistickou studii rozvojového území Holešovice-sever. Nové urbanistické řešení umožňuje vhodnější využití území elektrárny, které je obklopeno dvěma železnicemi. V tomto sevřenému cípu byl navržen zábavní park, kterému dominují historické objekty s nově navrženou dostavbou. Všechny tyto objekty jsou umístěny na pozemku v několika rovnoběžných liniích a vytváří tak vstupní bránu do areálu. Historické objekty jsou následně využity pro divadlo a galerii umění a designu. K objektu je napojena i novostavba restaurace a bowlingu, která cely komplex citlivě doplňuje a vytváří nový venkovní prostor okolo budov.

The master?s thesis elaborates the building of a former engine house and a boiler room in Holešovická Power station (Holešovická elektrárna), today there is a heating plant. It is a conversion of historical factory buildings that are now being used for culture and entertainment. The thesis follows a pre-diploma project that focused on an urban study of a developing area of Holešovice-north (Holešovice-sever). A new urban adaptation enables more convenient usage of the area of the Power station that is surrounded by two railways. In this constricted tip an amusement park that is dominated by historical buildings with a newly designed completion of the construction was designed. All of the buildings are located in several parallel lines and create a gateway to the compound. The historical buildings are subsequently used for the theatre and the gallery of art and design. The compound is linked with a new building with a restaurant and bowling. The building sensitively complements the whole complex and creates a new outdoor space around the buildings.
The Conversion of Holešovice Power Station
Keywords: konverze, elektrárna, Holešovice; conversion, power station, Holešovice